How effective is the new community-based Welsh low vision service?. Issue 2 (3rd July 2010) - Court, H; Ryan, B; Bunce, C; Margrain, T H
Abstract : Aims: To determine if there was a significant difference between user-centred and clinical outcomes in people with low vision who attended a new community-based low vision service (CLVS) or the hospital-based low vision service (HBLV). Methods: A prospective controlled before and after study. Participants were recruited from the CLVS (n=343; 96 male, 247 female; median age 82 years) and from the HLVS (n=145; 55 male, 90 female; median age 80 years). The primary outcome measure was change (baseline to 3 months) in visual disability as evaluated by the seven-item National Eye Institute-Visual Function Questionnaire (NEI-VFQ). Secondary outcome measures included: use of low vision aids, satisfaction with the service provided and change in near visual acuity before and after the provision of low vision aids. Results: There were no significant differences in user-centred and clinical outcome measures between the CLVS and HLVS. Self-reported visual disability was significantly reduced after low vision service intervention for participants in both groups by 0.46 and 0.57 logits in the HLVS and CLVS, respectively. Conclusion: This study provides strong evidence that CLVS and HLVS are effective methods of service provision in Wales.